Chronic Lymphocytic Leukemia Resulting in Hemorrhagic Brain Masses After Sepsis. (January 2020) - Gusdon, Aaron M.; Cho, Sung-Min; Mayasi, Yunis; Malani, Rachna; Püttgen, Hans A.; Duffield, Amy; Bolaños-Meade, Javier; Lim, Michael
Chronic lymphocytic leukemia (CLL) rarely results in central nervous system (CNS) involvement. When CLL does affect the CNS, it typically manifests as leptomeningeal involvement, not commonly causing parenchymal involvement unless having undergone a higher grade transformation. We report a case of a patient with untreated CLL who presented with a large right frontal hemorrhagic mass along with additional bilateral masses after being found unresponsive. He had recently been hospitalized with Staphylococcus aureus sepsis. His neurological examination improved after resection of the largest mass however deteriorated again with accumulation of blood in the resection cavity requiring evacuation of the blood products and placement of an external ventricular drain. Pathology from the initial resection revealed sheets of CD20 consistent with untransformed CLL. Additionally, there were areas of necrosis and gram-positive organisms. Given the unusual presentation with large hemorrhagic brain masses, we suspect that the antecedent bacteremia may have resulted in blood–brain barrier breakdown and seeding of the CNS parenchyma with CLL cells.